PONDOK PEDULI ANAK JALANAN - Lavia Lavia; Petrus Rudi Kasimun (Jurusan Arsitektur dan Perencanaan, 2021)
The condition of a child who does not have parents or a guide in life will be difficult to develop and grow well. It takes the right place for children to study together regardless of race, economy, and other problems. A place that becomes a home for children to learn and play together with the right people and understand very well about children's problems. Even parents always hope that their children can grow up to be children who have good and healthy personalities. But of course parents themselves are not perfect creatures who can teach it all. Because humans have their own skills and talents. Respectively Even having parents, there is no guarantee that parents really understand the child's condition. Very often parents do not understand or even pay less attention which of course affects the child's growth and development. Because humans naturally need other people to be role models or examples in their life. One solution that can address this problem is by designing a halfway house for street children that has appropriate facilities for child development, is environmentally friendly, and is located close to where street children are. Street children generally earn money on streets close to public transportation locations. some street children have been handled by an orphanage. However, the facilities and the number of orphanages are not proportional to the number of street children. So that not all street children can be handled properly. Designs are made not only for theoretical learning but also for developing other types of children's intelligence. The process of form and space is made according to the needs that will be needed by children in terms of health, hobby distribution, social interaction, and education. So that children can feel learning is not just a theory but can also be channeled into other forms of activity. Keywords: develop and grow well; house for street children; personalitites AbstrakKondisi anak yang tidak memiliki orangtua maupun penuntun dalam hidupnya akan sulit untuk berkembang dan tumbuh dengan baik. Diperlukan tempat yang tepat untuk anak dapat belajar bersama tanpa memandang ras, ekonomi, dan masalah lainnya. Tempat yang menjadi rumah untuk anak belajar dan bermain bersama dengan orang yang tepat dan paham betul tentang persoalan anak. Orangtua sekalipun selalu berharap anaknya dapat tumbuh menjadi anak yang memiliki kepribadian baik dan sehat. Tetapi tentunya orangtua sendiri bukan mahkluk sempuran yang dapat mengajarkan itu semua. Karena manusia memiliki keahlian dan bakat masing – masing. Bahkan memiliki orangtua sekalipun tidak ada jaminan orangtua mengerti betul tentang kondisi anak. Sering sekali orangtua kurang memahami atau bahkan kurang memberikan perhatian yang tentu saja berpengaruh terhadap tumbuh kembang anak. Karena sewajarnya manusia memerlukan orang lain untuk menjadi panutan atau contoh dalam hidupnya. Salah satu solusi yang dapat menangani masalah tersebut dengan merancang rumah singgah untuk anak jalanan yang memiliki fasilitas yang sesuai untuk perkembangan anak ,ramah lingkungaan, serta letaknya dekat dengan dimana anak jalanan berada. Anak jalanan pada umumnya mencari uang dijalan berdekatan dengan lokasi transpotasi umum. beberapa anak jalanan sudah di tangani oleh panti asuhan. Akan tetapi, fasilitas serta jumlah panti asuhan tidak sebanding dengan jumlah anak jalanan. Sehingga tidak semua anak jalanan dapat tertangani dengan baik. Rancangan dibuat tidak hanya untuk belajar secara teori melainkan mengembangkan jenis kecerdasaaan anak lainnya. Proses bentuk dan ruang dibuat menyesuaikan dengan kebutuhan yang akan dibutuhkan anak dari segi kesehatan, penyaluran hobi, interaksi sosial, dan edukasi. Sehingga anak dapat merasakan belajar tidak hanya sekedar teori akan tetapi juga dapat disalurkan dalam bentuk aktivitas lainnya.